Establishing the feasibility of a patient-engagement tool to improve outpatient symptom management and dosing of patients on regorafenib. Issue 28 (1st October 2022) - Mukherji, Reetu; Boudriga, Amani; Isenstein, Howard; Marshall, John
Abstract : 417 Background: Regorafenib (rego), an oral multikinase inhibitor, improves overall survival in patients (pts) with metastatic colorectal cancer (mCRC). However, its toxicity profile including, but not limited to, hand-foot skin reactions, fatigue, and hypertension significantly limits its use and often requires dose interruptions (40% rate) or modifications (20-25% rate). Inadequate symptom management can lead to frequent clinic visits, reduced quality of life, therapy non-adherence, and poor clinical outcomes. We aimed to establish the feasibility and usability of a CarePrompter smartphone application (app), a digital pt engagement tool with a pt and provider interface, to monitor and triage pt symptoms when starting rego. Methods: mCRC pts starting rego for the first time and with access to an iOS or Android smartphone with a data plan were recruited at MGUH. Pts were enrolled for the duration of their rego treatment. Once consented, recruiters downloaded and registered pts on the mobile app. Pts were provided a blood pressure (BP) cuff and trained on how to record their BP and answer a customized set of up to 17 questions daily on the app. The questions included documenting the status of the daily dose taken, completion of weekly labs, BP, whether pts needed advice, and severity of various side-effects if present on a 1-10 scale. Oncologists and nurses trained to use a CarePrompter triage tool were alerted when pts indicated missed doses, missed labs, high blood-pressure, high side-effect scores (8-10), and request for advice. Results: A total of 11 pts enrolled in the study. The study duration ranged from 1 to 5 months per pt. Pts, on average, completed the app questionnaire 10 out of 30 days, with the lowest rate of completion being 2 out of 30 days and the highest rate being 20 out of 30 days. BP recordings were logged an average of 10 times per pt in a 30-day period. An average of 2 provider alerts were triggered per pt. The alerts were primarily from pts documenting not performing labs or omitting rego doses. All alerts were acknowledged and resolved by a provider through the CarePrompter-triage tool. Providers found the tool usable based on qualitative interviews. There was an average dose increase of 1.25 rego pills from pt's start to end dose. While 62.5% of pts were treated with the highest dose (160 mg) at one point in their treatment, by the end of the study 25%, 50%, and 25% remained on 160 mg, 120 mg, and 80 mg doses, respectively. Conclusions: The CarePrompter mobile app was technically feasible and usable by cancer patients and providers in monitoring symptoms and addressing real-time ambulatory issues during rego dosing. Additional studies are warranted to determine if routine utilization of this app in clinic translates to enhanced patient experiences, toxicity management, daily dosing, therapeutic compliance, and survival.